ACUTE POISONING TREATED IN MEDICAL INTENSIVE CARE UNIT - Fawad Rahim; Fahim Ullah; Mohammad Haroon; Muhammad Ashfaq; Ayesha Khan Afridi (Gomal Journal of Medical Sciences, 2017)
Background: Acute poisoning including drug overdose is responsible for significant morbidity and mortality. The objectives of this study were to determine the frequency and distribution of acute poisoning in set up of a medical intensive care unit. Material & Methods: This was a record based, cross-sectional study conducted at Medical ICU of Khyber Teaching Hospital, Peshawar, Pakistan from Feb. 1, 2015 to March 15, 2015. Ninty two patients with acute poisoning admitted to medical ICU between March 2009 and October 2014 were included. The demographic variables were; gender, age in years and marital status. The research variables were; the type of poisons, the number of poisons, route of poisons, mode of poisons, the need for ventilatory, inotropic and renal support, duration of stay, and outcome of patients. Counts and percentages were calculated for the nominal and means and SDs for numeric variables. Chi-square goodness of fit test was applied. Results: Out of total of 92 patients, 55 (59.8%) were females and 37 (40.2%) were males with female to male ratio of 1.49:1. The mean age of the sample was 26.8±13.9 years. The mean duration of stay for the sample was 3.14±0.52 days. The differences of counts (frequencies) among different attributes of all the ten nominal variables except gender were statistically significant, assuming that all attributes have equal expected counts. Conclusion: Acute poisoning is a common medical emergency. These patients commonly need ventilatory and inotropic support, and have high mortality rates. Proper triage and timely admission to intensive care unit may improve outcome of these patients.